Pedagogical Principles of Organizing and Management of Technological Education (Web of Technology: Multidimensional Research Journal, 2023)
In this article, the pedagogical principles of organizing and managing technological education in general education schools: in particular, the appropriate use of methods and methods in the process of technology education, the principles of students' use of technology in technological education are clarified and analyzed. The essence of these principles in determining the strategy of technological education is revealed.